Design of transparent microstrip grid array antenna - N. I. Mohd Ali; N. Misran; M. F. Mansor; M. F. Jamlos (Institute of Advanced Engineering and Science, 2019)
A transparent grid array antenna of 28 GHz frequency is presented. The radiating element of the antenna is made of ITO thin film and printed on a glass as the dielectric substrate. The simulation of the antenna executed by using Computer Simulation Technology (CST) Microwave Studio software demonstrated at 28 GHz operating frequency for 5G band applications. This antenna then compared to the rectangular microstrip patch antenna of the same operating frequency. Structural parameters of the proposed antenna were optimized based on parametric studies done. Grid array antenna gives better performance as it gives 35.7% lower return loss with -43.88 dB, better efficiency and gain with a gain of 7.358 dB, which is more than 40% increases.